Use of Biopolymeric Membranes for Adsorption of Paraquat Herbicide from Water - Cocenza, Daniela Sgarbi [UNESP]; de Moraes, Mariana A.; Beppu, Marisa M.; Fraceto, Leonardo Fernandes [UNESP] (Springer, 2012)
The use of membranes prepared with alginate and chitosan to adsorb paraquat aqueous solution was evaluated as a potential alternative technique for remediation of contaminated water. Production of bilayer membranes was based on the electrostatic interaction between alginate (a polyanion) and chitosan (a polycation). Herbicide adsorption experiments were performed using three different membranes, consisting of pure alginate, pure chitosan, and a chitosan/alginate bilayer. Adsorption was characterized using the Langmuir and Freundlich isotherm models, as well as by applying pseudo-first order and pseudo-second order kinetic models. The potential use of the membranes in environmental applications was evaluated using water collected from the Sorocabinha River in So Paulo State, Brazil. The results indicated that interactions between the membranes and the herbicide were strongly related to the type of biopolymer and the physical-chemical characteristics of the herbicide.
Keywords: Herbicides; Water contamination; Adsorption; Membranes; Natural polymers